Improving the Effectiveness of Public Finance : Cambodia Public Expenditure Review - World Bank Group (World Bank, Washington, DC, 2019)
Cambodia’s rapid economic growth and poverty reduction have taken place in an environment characterized by macroeconomic stability and prudent fiscal management. Having recently graduated to become a lower middle-income country, Cambodia is beginning to face complex fiscal and public service delivery challenges. The Cambodia public expenditure review (PER) discusses the numerous achievements in fiscal policy to date and presents policy options going forward, based on both analysis and consultations with stakeholders. The PER aims to help the Royal Government of Cambodia in the effort to overcome the challenges and move toward more effective public spending and service delivery, while maintaining macroeconomic stability. To make the most of fiscal policy and available fiscal space, Cambodia needs to continue improving the allocation and execution of public resources, for increased value for money. The Cambodia Public Expenditure Review (PER)discusses the numerous achievements in fiscal policy to date and proposes policy options goingforward, based on both analysis and consultations with stakeholders. The PER aims to help the RoyalGovernment of Cambodia in the effort to overcome the abovementioned challenges and move towardmore effective public spending and service delivery, while maintaining macroeconomic stability. Structured around the key challenges, the six chapters of the PER are based on background papers that incorporate feedback from two rounds of consultations with the PER Committee chaired by the Ministry of Economy and Finance.